Gene Transfer Agents in Bacterial Endosymbionts of Microbial Eukaryotes. (23rd June 2022) - George, Emma E; Tashyreva, Daria; Kwong, Waldan K; Okamoto, Noriko; Horák, Aleš; Husnik, Filip; Lukeš, Julius; Keeling, Patrick J
Abstract: Gene transfer agents (GTAs) are virus-like structures that package and transfer prokaryotic DNA from donor to recipient prokaryotic cells. Here, we describe widespread GTA gene clusters in the highly reduced genomes of bacterial endosymbionts from microbial eukaryotes (protists). Homologs of the GTA capsid and portal complexes were initially found to be present in several highly reduced alphaproteobacterial endosymbionts of diplonemid protists ( Rickettsiales and Rhodospirillales ). Evidence of GTA expression was found in polyA-enriched metatranscriptomes of the diplonemid hosts and their endosymbionts, but due to biases in the polyA-enrichment methods, levels of GTA expression could not be determined. Examining the genomes of closely related bacteria revealed that the pattern of retained GTA head/capsid complexes with missing tail components was common across Rickettsiales and Holosporaceae ( Rhodospirillales ), all obligate symbionts with a wide variety of eukaryotic hosts. A dN/dS analysis of Rickettsiales and Holosporaceae symbionts revealed that purifying selection is likely the main driver of GTA evolution in symbionts, suggesting they remain functional, but the ecological function of GTAs in bacterial symbionts is unknown. In particular, it is unclear how increasing horizontal gene transfer in small, largely clonal endosymbiont populations can explain GTA retention, and, therefore, the structures may have been repurposed in endosymbionts for host interactions. Either way, their widespread retention and conservation in endosymbionts of diverse eukaryotes suggests an important role in symbiosis.